The influence of capital intensity, earnings management and audit committee on tax avoidance - Senny, Nila; Hernawati, Erna (Educoretax, 2025)
This study aims to determine the effect of capital intensity, earnings management, and audit committees on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange. Using company financial and annual report data from 2019 to 2023, this study applies purposive sampling techniques and STATA 12 applications to process the existing data. The results of this study indicate that capital intensity has a negative effect on tax avoidance, and companies with higher levels of capital intensity are less likely to engage in aggressive tax avoidance. Conversely, earnings management has a positive impact on tax avoidance, because companies that engage in earnings management are more likely to engage in tax avoidance. And the audit committee has a positive effect on tax avoidance, where although the audit committee should play a role in reducing tax avoidance, research shows that an ineffective audit committee can actually exacerbate tax avoidance. This research is expected to contribute to the formulation of tax policies and corporate supervision to minimize tax avoidance.